CHARACTERISTIC OF FROZEN-THAWED EPIDIDYMAL SPERMATOZOA AND REFRIGERATED STORAGE OF RAM SPERMATOZOA - Karja, N.W.K.; Respaty, E.M.A.; Nuraini, I.; Prihatno, S.A.; Gustari, S. (Journal of the Indonesian Tropical Animal Agriculture, 2010)
Post-mortem spermatozoa recovery is an important technique for obtaining germplasm reservesfrom genetically valuable animals or endangered species. The purpose of this study was to studywhether ram spermatozoa within epididymides stored at 4º C for 24 and 48 h remain their motility andviability. The characteristic of ram epididymal spermatozoa after freezing and thawing was alsoobserved. Six pairs of ram testes with attached epididymides were used in this study. The motility ofcontrol spermatozoa was well maintained throughout the dilution procedure (83.3±1.1, 80±1.3, and80±1.3% for collection, Niwa and Sasaki freezing -1 extender (NSF-1 and NSF-2 groups respectively);but declined (P<0.05) after freezing and thawing (38.3±3.1%). Motile and viable spermatozoa could berecovered from epididymides up to 48 h of storage, although their quality declined significantly(P<0.05) as post-mortem storage time increased (motility: 83±1.2, 67±3.0, and 46±5.1; viability:84.2±2.4, 73±2.8, and 66.6±2.6 % for control, 24 h and 48 h group respectively). These data indicatethat ram epididymides could be stored at 4º C for 48 h when epididymal spermatozoa cannot beimmmediately collected and cryopreserved. These storage conditions might be possible to use forepididymal sperm recovery in wild ruminants.